Effect of Glibenclamide and Tomato lycopene extract on some biochemical parameters in serum of alloxan Induced diabetic rabbits - Ayhan R. Mahmood; Mohammed Sh. Abdulla; EntedharR. Sarhat (Kirkuk Journal of Science, 2015)
Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycaemia resulting from defects in insulin secretion, insulin action, or both, and occurs in almost all populations of the world a variable prevalence. In the present study we evaluated the effect of glibenclamide, and tomato lycopene extract on blood glucose, enzymatic antioxidants, glycated hemoglobin(HbA1c), and malondialdehyde(MDA) in 50 alloxan induced diabetic rabbits. The results showed a significant(P < 0.001) increase in the level of glucose, HbA1c, MDAin alloxan diabetic rabbits in comparison to the control rabbits. A Significant decrease in the level of serum glucose, HbA1c,and MDAin alloxan diabetic rabbits when received glibenclamide daily as single dose 0.5 mg/kg body weight for 20 weeks, and2and 4 mg/kg of tomato lycopene extract for 20 weeks respectively. The result of this study showed a significant (P